1995
DOI: 10.1021/ja00141a011
|View full text |Cite
|
Sign up to set email alerts
|

Shape and stereoselective cyclopropanation of alkenes catalyzed by iron porphyrins.

Abstract: Iron porphryin complexes are active catalysts for the cyclopropanation of alkenes by ethyl diazoacetate. Fe(TIP) (TIP = meso-tetra-p-tolylporphyrin), an isolated iron(II) porphyrin complex, can be used as the catalyst, or the iron(III) complexes of several porphyrins can be reduced in situ. The reactions produce synthetically useful excesses of the trans cyclopropyl ester products. This stereoselectivity exhibits a modest solvent dependence, with donor solvents giving higher ratios of the trans cyclopropane pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
193
2
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(227 citation statements)
references
References 1 publication
(1 reference statement)
27
193
2
2
Order By: Relevance
“…A particularly interesting set of reactions proceeds through metal-carbenoid intermediates that had never been exploited for catalysis by heme proteins. The synthetic porphyrin systems relied on synthetic activated reagents such as ethyldiazoacetate (EDA) to generate the metal carbenoid, which could then react with olefins or insert the carbene into various N-H, C-H, or O-H bonds (Baumann et al 2007;Chen et al 2004;Wolf et al 1995). That the metal-carbenoid intermediate resembles compound I in the native P450 catalytic cycle (Fig.…”
Section: New Enzymes From Old: Adding To the Cytochrome P450's (Alreamentioning
confidence: 99%
“…A particularly interesting set of reactions proceeds through metal-carbenoid intermediates that had never been exploited for catalysis by heme proteins. The synthetic porphyrin systems relied on synthetic activated reagents such as ethyldiazoacetate (EDA) to generate the metal carbenoid, which could then react with olefins or insert the carbene into various N-H, C-H, or O-H bonds (Baumann et al 2007;Chen et al 2004;Wolf et al 1995). That the metal-carbenoid intermediate resembles compound I in the native P450 catalytic cycle (Fig.…”
Section: New Enzymes From Old: Adding To the Cytochrome P450's (Alreamentioning
confidence: 99%
“…This experimental result can be due to the formation of a transition state in which the phenyl group of styrene is pushed far away from the ester group of the carbene intermediate already pointing towards the orthomethoxy groups of the aryl moieties. [34] According to the authors, this process is more difficult for norbornene because of its low flexibility, consequently the stereoselectivity of the reaction is controlled by the steric interactions between the olefin and the porphyrin, and a higher cis/trans ratio was obtained. This effect was enhanced when methoxy groups were replaced by chlorine to give complex 3.…”
Section: Rhodium-catalysed Reactionsmentioning
confidence: 99%
“…35 In fact, we observed that iron heme in aqueous buffer, with no protein, can catalyze the formation of 3a, albeit with only 0.4 TTN. This basal activity is greatly enhanced and stereoselectivity is enforced by the protein environment, allowing the heme proteins described here to cyclopropanate a range of alkenes from electronrich conjugated dienes to electron-deficient vinyl ketones and acrylates with high diastereo-and enantioselectivity.…”
mentioning
confidence: 78%